Implementasi Pendidikan Akhlak KH. Abd Wahab Hasbullah di MAUWH Bahrul Ulum Tambakberas Jombang - umi khulsum; Didin Sirojudin (JoEMS (Journal of Education and Management Studies), 2019)
These days akhlak education have started to hollowed, so there is a need to provide perpetual study about these. The purpose of this study is to know how the implementation of akhlak education according to KH Abd Wahab Hasbullaj in Madrasah Aliyah Unggulan KH Abd Wahab Hasbullah Bahrul Ulum Tambakberas Jombang, because it is one of the school which using the name of Kyai Wahab as its name. This study is a study using qualitative approach with library research as a main metode. Some of the akhlak of KH Abd Wahab Hasbullah are: his attention towards NU organization, dicipline, presevering, diligent, generous, merciful, kind, friendly, have broad knowledge, nationalist, have forward tought, and firm. While the implication of akhlak education according to KH Abd Wahab Hasbullah in Madrasah Aliyah Unggulan KH abd Wahab Hasbullah Tambakberas Jombang have been applied, it is proved that these are included in the vision and mission of the Madrasah, which is the implementation of modeled akhlak education from KH Abd Wahab Hasbullah, that is producing 'smart, right, professional, environment carer, and pious to God' generation, which all of these things are inside the figure of KH Abd Wahab Hasbullah himself.